2020
DOI: 10.3390/v12040447
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Suppresses Tsg101 Recognition of Ub-Modified Gag and Facilitates Recruitment to the Plasma Membrane

Abstract: The ESCRT-I factor Tsg101 is essential for sorting endocytic cargo and is exploited by viral pathogens to facilitate egress from cells. Both the nucleocapsid (NC) domain and p6 domain in HIV-1 Gag contribute to recruitment of the protein. However, the role of NC is unclear when the P(S/T)AP motif in p6 is intact, as the motif recruits Tsg101 directly. The zinc fingers in NC bind RNA and membrane and are critical for budding. Tsg101 can substitute for the distal ZnF (ZnF2) and rescue budding of a mutant made de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 61 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…The p6 domain is known to be involved in the recruitment of host factors, such as Tsg101 (Tumor susceptibility gene 101) and ALIX (ALG-2 interacting protein X), and ubiquitination of those factors strongly promote viral budding [ 135 ]. In this frame, fusion experiments in which the p6 domain was coupled with Ub showed that the affinity of Tsg101 for p6 in this case results in being strengthened [ 136 ], and the ubiquitination of Pr55 Gag can increase Tsg101 recruitment [ 137 ]. Besides, Tsg101 displays an N-terminal Ub E2 variant (UEV) domain that shows homology with E2 Ub ligases, and that can specifically bind Ub proteins, as well the PTAP late domain in Pr55 Gag [ 136 ].…”
Section: Hiv-1 Pr55 Gag Ubiquitinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The p6 domain is known to be involved in the recruitment of host factors, such as Tsg101 (Tumor susceptibility gene 101) and ALIX (ALG-2 interacting protein X), and ubiquitination of those factors strongly promote viral budding [ 135 ]. In this frame, fusion experiments in which the p6 domain was coupled with Ub showed that the affinity of Tsg101 for p6 in this case results in being strengthened [ 136 ], and the ubiquitination of Pr55 Gag can increase Tsg101 recruitment [ 137 ]. Besides, Tsg101 displays an N-terminal Ub E2 variant (UEV) domain that shows homology with E2 Ub ligases, and that can specifically bind Ub proteins, as well the PTAP late domain in Pr55 Gag [ 136 ].…”
Section: Hiv-1 Pr55 Gag Ubiquitinationmentioning
confidence: 99%
“…Besides, Tsg101 displays an N-terminal Ub E2 variant (UEV) domain that shows homology with E2 Ub ligases, and that can specifically bind Ub proteins, as well the PTAP late domain in Pr55 Gag [ 136 ]. During assembly, the interaction of Pr55 Gag with the PM promotes the intermolecular interaction between Tsg101 and the PTAP domain in Pr55 Gag [ 137 ]. In this conformation, the di-ubiquitinylated K63 of Tsg101 was found to interact with p6, with the consequence of impairing the potential polyubiquitination of the precursor at PM [ 137 ].…”
Section: Hiv-1 Pr55 Gag Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This polymerization activates VPS-4, an ATP free hydrolase, which in turn disassembles the ESCRT-III domain by hydrolyzing its proteins leading to the pinching off of the virion from the PM [172]. A recent study has reported that the proper recruitment of Tsg101 by PTAP is further controlled by RNA (probably bound to NC domain) and that the latter prevents Gag polyubiquitination and thus its degradation [183].…”
Section: P6 Domain Of Hiv-1 Gagmentioning
confidence: 99%
“…The UEV domain mediates these Tsg101 functions through the P(T/S)AP-and Ub-binding functions. The region downstream of the UEV domain in Tsg101 interacts with other proteins, including the binding partners with which it forms ESCRT-I, a complex that functions with ESCRT-0, -II, -III, and the ATPase Vps4 in endocytic trafficking (reviewed in [4,6,14,15]). As the member on which the partners nucleate, Tsg101 thus controls ESCRT-I formation and plays an essential scaffolding and mechanical role in addition to functioning as a conduit to ESCRT-III [8].…”
Section: Introductionmentioning
confidence: 99%